Supramolecular Chemistry of Click Linear Oligo- and Poly-(amide-triazole)s - Chow, Hak-Fun; Chui, Tin-Ki; Qi, Qiuli (Synlett, 2014)
This account summarizes our ongoing studies on the synthesis and properties of oligo- and poly(amide-triazole)s. Various structural factors, such as dipole–dipole interactions, polymer side-chain effects and zip-templating effects that can influence the supramolecular self-assembly process are revealed. The unique attributes of these multifunctional compounds as gelating and chemosensing materials are discussed.1 Background2 Linear Oligo(amide-triazole) Compounds Derived from Oligopeptides3 Linear Oligo(amide-triazole) Compounds Derived from Oligo- and Polyamides4 Conclusions and Outlook
Keywords: self-assembly; supramolecular chemistry; amides; cycloaddition; heterocycles